Preface - Nowak, Andrzej N. (Computer Assisted Methods in Engineering and Science, 2015)
This special issue of the Computer Assisted Methods in Engineering and Science and the papers in the already published special issue CAMES 3/2015 comprise selected papers presented during the Eurotherm Seminar No 109 – Numerical Heat Transfer 2015. This conference was organised under the auspices of the EUROTHERM Committee on 27–30 September, 2015 in Warsaw, Poland. The aim of the EUROTHERM Committee is to promote and foster European cooperation in thermal sciences and heat transfer by gathering together scientists and engineers working in specialised areas.